ACTUALIZATION OF IDEAS OF FREE EDUCATION NEWLY PERSONALLY ORIENTED PEDAGOGICAL TECHNOLOGIES - Kalinichenko, T.F. (Pedagogy of Higher and Secondary Education, 2004)
This article a reveals of free upbringing ideas and investigation the principles modern pedagogic technology of personally oriented approach to organization of upbringing of youth.